Ethyl 2-[(2-hydroxybenzylidene)amino]-6-methyl-4,5,6,7-tetrahydrothieno[2,3-c]pyridine-3-carboxylate - Naki Çolak; Dursun Ali Köse; Nazmiye Marım; Ömer Çelik; Tuncer Hökelek (Acta Crystallographica Section E, 2013)
The title compound, C18H20N2O3S, exists as the phenol–imine form in the crystal and there are bifurcated intramolecular O—H...(N/O) hydrogen bonds present. The conformation about the C=N bond is anti (1E); the C=N imine bond length is 1.287 (4) Å and the C=N—C angle is 122.5 (3)°. In the tetrahydrothienopyridine moiety, the six-membered ring has a flattened-boat conformation. In the crystal, molecules are stacked nearly parallel to (110) and a weak C—H...π interaction is observed. The carbonyl O atom is disordered over two positions and was refined with a fixed occupancy ratio of 0.7:0.3.